A 12-Week Strict Low FODMAP Diet Reduces the Severity Levels of Fatigue, Depression, Anxiety, and Inattention in Patients with Irritable Bowel Syndrome - Sol Maja G Bjørkevoll; Eline M Randulff Hillestad; Gülen A Lied; Erica S Teige; Elisabeth K Steinsvik; Birgitte Berentsen; Astri J Lundervold (Current Developments in Nutrition, 2025)
Background: The low FODMAP diet (LFD) has been shown to alleviate gastrointestinal symptoms in patients with irritable bowel syndrome (IBS). However, the impact of the LFD on coexisting symptoms of fatigue, anxiety, depression, and cognitive functions remains unclear. Objectives: This study aims to investigate the effects of a 12-wk strict LFD on symptoms of fatigue, depression, anxiety, and inattention in patients with moderate-to-severe IBS-D (diarrhea-predominant), and IBS-M (mixed diarrhea and constipation). Methods: Participants with IBS were included in an open-label, single-center, 12-wk dietary intervention conducted at Haukeland University Hospital in Bergen, Norway. They followed a strict LFD guided by a registered dietitian and completed questionnaires assessing fatigue [Chalder Fatigue Scale (CFQ-11)] and anxiety and depression [Hospital Anxiety and Depression Scale (HADS)] and performed a test of attention [the third edition of the Connors’ continuous performance test (CPT-3)] at baseline and 12-wk follow-up. Data were analyzed using Wilcoxon signed-rank tests to evaluate changes from baseline to post intervention. Results: Thirty-six participants completed the intervention. Statistically significant reductions were observed in symptoms of fatigue (CFQ-11, P < 0.013) and symptoms of anxiety (HADS-A, P < 0.006). Most of the patients were defined as noncases of fatigue and anxiety following the intervention. Performance on the CPT-3 revealed improvements in measures of inattention. Conclusions: A 12-wk strict LFD intervention significantly alleviated coexisting symptoms of fatigue, anxiety, and depression, and improved performance on a psychometric test of attention. These findings suggest that dietary management plays a crucial role in improving both physical and mental health in patients with IBS.This study was registered at clinical trial as NCT04296552 (https://clinicaltrials.gov/study/NCT04296552?term=NCT04296552&rank=1).